Rice Farmer Risk Management by Cropping Pattern Diversification in Rural West Java: Motivation, Behavior, and Perception - Dadang Jainal Mutaqin; Koichi Usami (The Journal of Indonesia Sustainable Development Planning, 2020)
The Indonesian government have implemented agricultural production cost insurance since 2015 called Asuransi Usaha Tani Padi (AUTP). It is an issue that the rate of farmer participation in the insurance is still low. As a challenge to increase participation, it becomes important to be aware of motivation, behavior, and perception that influence the practical risk management of farmers. This study investigated the relationship between cropping pattern diversification (as risk management) and factors such as motivation, behavior, and perception. Based on a field survey of 240 smallholder farmers in Garut District, West Java Province, these were the characteristics of farmers who practiced cropping pattern diversification: (1) high-risk perception (impact and probability); (2) risk-averse; and (3) economic motivation. The study revealed that approximately one-third of farmers had risk-neutral and low-risk perceptions of whom approximately 70.7 percent practiced single cropping patterns. They may not adopt any risk- coping strategies unless they are aware of the risks that they face. Improving awareness about the negative impacts of risks on income from farming might encourage them to adopt risk-coping strategies for both on-farm risk coping (such as cropping pattern diversification) and off-farm risk-coping (such as agricultural insurance).